2016
DOI: 10.1002/rcs.1765
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric measurement of the cervical spine for minimally invasive pedicle screw fixation using reverse engineering and three‐dimensional reconstruction

Abstract: The measurements of this study could provide detailed information for percutaneous cervical screw fixation. The data of the relationship between the cervical spinous process and the pedicle screw channel present valuable technical information for the design, optimization and clinical application of the aiming device for percutaneous cervical pedicle screw fixation. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…22,27 Abumi 11,13 suggested that the optimum medial angle for PS placement should be 308 to 408 and the maximum angle range is 258 to 458. Zhou et al 34 measured the 3D reconstruction model of subaxial cervical CT scans and found that the medial angle for minimally invasive PS placement was 32.938 to 35.648, which is consistent with our results. According to the reports of Karaikovic, Panjabi, and Bozbuga 22,23,27 on the measurements of cervical pedicle, the width of each cervical pedicle at C3-C7 vertebrae is always smaller than its height.…”
Section: Screw Anglesupporting
confidence: 91%
“…22,27 Abumi 11,13 suggested that the optimum medial angle for PS placement should be 308 to 408 and the maximum angle range is 258 to 458. Zhou et al 34 measured the 3D reconstruction model of subaxial cervical CT scans and found that the medial angle for minimally invasive PS placement was 32.938 to 35.648, which is consistent with our results. According to the reports of Karaikovic, Panjabi, and Bozbuga 22,23,27 on the measurements of cervical pedicle, the width of each cervical pedicle at C3-C7 vertebrae is always smaller than its height.…”
Section: Screw Anglesupporting
confidence: 91%
“…It is also a transitional vertebra between the cervical vertebra and the thoracic vertebra [ 2 ]. In multisegmental fixation of the cervical spine, C7 is usually the most caudal point and the site of the highest concentration of stress [ 4 ]. Therefore, pedicle screw (PS) fixation is the optimal choice.…”
Section: Introductionmentioning
confidence: 99%